Nutritive and bioactive properties of mesquite (prosopis pallida) flour and its technological performance in breadmaking - Gonzales-Barron, Ursula (2018)
﻿Although the nutritional profile, bioactivities, and uses of mesquite pod flour from various Prosopis species have been studied, limited research has been conducted on Prosopis pallida (Humb, & Bonpl. Ex Willd.) Kunth mesquite flour. This study aimed to characterize the nutritional quality and bioactive properties of P. pallida pod flour and to assess its technological performance in breadmaking as a partial replacer of white wheat flour. Peruvian P. pallida mesquite flour was found to have an appealing nutritional profile, with high contents of dietary fiber (29.6% dw) and protein (9.5% dw), and low contents of fat (1.0% dw) and carbohydrates (57.6% dw). It is a source of palmitic (12.6%), oleic (35.5%), and linoleic acids (45.8%), -, -, and - tocopherols, and contains phenolic compounds such as apigenin glycoside derivatives with proven antioxidant capacities. Extracts of P. pallida flour were also found to have antimicrobial and antifungal e ects and did not show hepatoxicity. When formulated as a wheat flour replacer, increasing mesquite flour levels yield composite doughs of lower stickiness and extensibility, and composite breads of lower elasticity (p < 0.01). However, up to a level of 10%, mesquite flour significantly increases loaf volume, reduces crumb hardness, and produces a more uniform crumb of small size alveoli (p < 0.01). Considering the purpose of improving the nutritional and technological quality of wheat flour bread, the addition of P. pallida pod flour can be highly recommended.